Genotypic Differences in Phosphorus Efficiency and the Performance of Physiological Characteristics in Response to Low Phosphorus Stress of Soybean in Southwest of China - Zhou, Tao; Du, Yongli; Ahmed, Shoaib; Liu, Ting; Ren, Menglu; Liu, Weiguo; Yang, Wenyu (Frontiers in Plant Science, 2016)
Southwest of China is one of the major soybean (Glycine max L.) production regions in China with low availability of soil phosphorus (P). Whereas little information is available on assessment of P-efficient soybean genotypes in this region, even though use of P-efficient soybean genotypes is a sustainable P management strategy for enhancing yield and P use efficiency. To assess the genetic variation on P use efficiency, 274 soybean genotypes were employed to compare the yield and P acquisition potentials in the field. Additionally, 10 representational genotypes (5 P-efficient genotypes and 5 P-inefficient genotypes) were grown in hydroponic media containing low P treatment (0.05 mM L-1) and high P treatment (0.25 mM L-1) to further investigate P assimilation characteristics and the related mechanisms of P-efficient soybean genotypes. In the field trial the models described the relationships between yield and seed P concentration (R2= 0.85), shoot P accumulation (R2= 0.84), HI (R2= 0.82) well. The yield, seed P concentration and shoot P accumulation ranged from 5.5 to 36.0 g plant-1, concentration from 0.045 to 0.93 % and accumulation from 0.065 to 0.278 mg plant-1, respectively. In the hydroponic trial, P-efficient genotypes under low P treatment showed significantly greater plant growth and higher P accumulation than P-inefficient genotypes. Simultaneously, total root length, specific root length, root surface area and root volume of P-efficient were significantly greater than P-inefficient under low P treatment. Higher rate of organic acid exudation and acid phosphatase activities were observed in the P-efficient soybean genotypes under low P condition when compared to the P-inefficient soybean genotypes. It indicated that significant genetic variation for P use efficiency existed in this region, and the P-efficient soybean genotypes, especially E311 and E141, demonstrated great tolerance to P deficiency, which could be potential materials using in improving production and P use efficiency in low availability of soil P region.